2019
DOI: 10.1007/s00787-019-01283-y
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant treatment profiles predicting co-occurring substance use disorders in individuals with attention-deficit/hyperactivity disorder

Abstract: Adolescents with attention-deficit/hyperactivity disorder (ADHD) are at increased risk of developing substance use disorders (SUDs) and nicotine dependence (ND). It remains unclear whether and how stimulant treatment may affect this risk. We aimed to investigate how stimulant use profiles influence the risk of SUDs and ND, using a novel data-driven community detection analysis to construct different stimulant use profiles. Comprehensive lifetime stimulant prescription data and data on SUDs and ND were availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
(37 reference statements)
5
24
0
2
Order By: Relevance
“…For instance, a study showed that early and consequent treatment with stimulants can decrease the risk for subsequent smoking, daily smoking, and AUD/SUD. Therefore, it can be hypothesized that undertreatment of ADHD may lead to more symptoms or increased rates of comorbidity, which in turn increases the risks for these 3 outcomes [52]. Similarly, comorbid ADHD complicates treatment of SUD [53].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study showed that early and consequent treatment with stimulants can decrease the risk for subsequent smoking, daily smoking, and AUD/SUD. Therefore, it can be hypothesized that undertreatment of ADHD may lead to more symptoms or increased rates of comorbidity, which in turn increases the risks for these 3 outcomes [52]. Similarly, comorbid ADHD complicates treatment of SUD [53].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood ADHD is a prominent risk factor for substance misuse and the development of SUD in adolescence and early adulthood, even when the most common comorbidities during childhood – conduct disorder and oppositional defiant disorder – are accounted for (e.g., [3, 4]). Some studies suggest that stimulant treatment of children with ADHD has a protective effect on the development of SUD in adolescence and early adulthood (e.g., [5, 6]), but other studies did not find such a protective effect (e.g., [7, 8]).…”
Section: Introductionmentioning
confidence: 99%
“…ADHD medication could be examined also regarding its direct effect on response inhibition in general. Since individuals with AUD or ADHD show impaired response inhibition, and stimulant treatment of ADHD in children might help to prevent later SUDs ( 88 ), a stimulant medication could be beneficial for those individuals with AUD or ADHD to improve inhibitory control. Not only should a treatment of AUD or ADHD per se be considered, but also the inhibitory deficits through medication or behavioral training should be addressed specifically.…”
Section: Discussionmentioning
confidence: 99%